In Vitro Anti-inflammatory Effect of Secretome from Umbilical Cord-derived Mesenchymal Stem Cells in COVID-19 Patient Blood: A Study on sIL-6R, sgp130, IL-1RA and Anti/pro Inflammatory Cytokines - Asysyifa, Nisrina; Wibowo, Heri; Abdullah, Murdani; Liem, Isabella Kurna; Bustami, Arleni (Newinera Publisher, 2024)
COVID-19 exhibits a wide range of clinical manifestations which severity of the disease is linked to uncontrolled escalation of inflammatory mediators. Ongoing research has identified the immunomodulatory effects of the MSC-derived secretome as a potential therapy for COVID-19. However, the precise mechanism by which the secretome exerts its therapeutic effect on COVID-19 remains unclear. This study aims to investigate whether the components of the UC-MSC-derived secretome can alter the inflammatory characteristics of immune cells. To achieve this, an in vitro study will be conducted involving co-incubation of whole blood with secretomes, followed by LPS stimulation. A total of 12 blood samples from severe COVID-19 and healthy subjects were cultured into three groups (RPMI control, 3μl and 9μl secretome group) incubated for 24 hours. Then, the cultures were exposed to LPS for 48 hours. The levels of sIL-6R, sgp130, IL-1RA, IL-6, TNF-α, IFN-γ, and IL-10 were measured. Results showed that LPS increased IL-6, TNF-α, and IL-10 production, while reducing sIL-6R, and sgp130, but no changes seen in IFN-γ in secretome-incubated blood cultures. The post-LPS/pre-LPS ratio analysis was conducted to investigate the anti-inflammatory potential of secretome. It was found that the secretome provides its anti-inflammatory effects through the role of IL-1RA.